2015
DOI: 10.1037/lat0000040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of perceived ethnic discrimination in the Hispanic Community Health Study/Study of Latinos Sociocultural Ancillary Study.

Abstract: Empirical studies examining perceived ethnic discrimination in Latinos of diverse background groups are limited. This study examined prevalence and correlates of discrimination in a diverse sample of U.S. Latinos (N=5,291) from the multi-site Hispanic Community Health Study/Study of Latinos (HCHS/SOL) and HCHS/SOL Sociocultural Ancillary Study. The sample permitted an examination of differences across seven groups (Central American, Cuban, Dominican, Mexican, Puerto Rican, South American, and Other/Multiple Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 47 publications
4
85
0
Order By: Relevance
“…In recognition of their growing prominence and unique constellation of structural disadvantages, Latinos occupy an important place in this nascent literature (Arellano-Morales et al 2015; Becerra et al 2013; Flippen and Parrado 2015; AUTHOR, DATE). 1 But because fully half of Latino adults are foreign born, continued progress in understanding their experience with discrimination requires expansion of theoretical and analytic frameworks (Krogstad and Lopez 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recognition of their growing prominence and unique constellation of structural disadvantages, Latinos occupy an important place in this nascent literature (Arellano-Morales et al 2015; Becerra et al 2013; Flippen and Parrado 2015; AUTHOR, DATE). 1 But because fully half of Latino adults are foreign born, continued progress in understanding their experience with discrimination requires expansion of theoretical and analytic frameworks (Krogstad and Lopez 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ethnoracial group membership can be viewed as a potential master status that intersects with other statuses such as gender, age, socioeconomic position, and authorization to live in the United States (Arellano-Morales et al 2015). Because statuses that shape social interactions and access to opportunities overlap, discrimination based on one form of disadvantage may increase in the presence of another form of disadvantage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that other factors, such as psychosocial stressors and discrimination, play an important role in the association between immigration history and inflammation. Previous research in Hispanic populations have shown that as Hispanic immigrants live in the US longer and become more acculturated, they also self-report experiencing greater exposure to psychosocial stressors (Arellano-Morales et al, 2015; Perez et al, 2008), which have documented links to inflammation (Cunningham et al, 2012; Kershaw et al, 2016b; Lewis et al, 2010). Unfortunately, our study did not collect data on exposure to discrimination; therefore, it is important for future work to explore the role of discrimination in the association between immigration status and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of discrimination were reported for Hispanic immigrants living in US longer and among second and third Hispanic immigrants (Perez et al, 2008). Similarly, the prevalence of reported discrimination was higher among US-born Hispanics (vs. to foreign-born Hispanics) and Hispanics with ≥10 years of US residence (Arellano-Morales et al, 2015). …”
Section: Introductionmentioning
confidence: 98%